'You can't move in Hackney without bumping into an anthropologist': why certain places attract research attention. (October 2016) - Neal, Sarah; Mohan, Giles; Cochrane, Allan; Bennett, Katy
In social research some places and populations are disproportionately targeted by researchers. While relatively little work exists on the concept of over-research those accounts that do exist tend to focus on participant-based research relationships and not place-based research relationships. Using interdisciplinary approaches and fieldwork experiences from a recently completed qualitative study of urban multiculture in England we develop the over-research debates in three key ways. First, the notion of 'over-research' carries negative connotations and we reflect on these as well as the possibility of more nuanced readings of research encounters. Second, we develop a more relational analysis, in which place – the London Borough of Hackney – is understood to be an animating force in the research process. Third, we argue that our experiences of the research provide evidence that many of the participants in the project were adept and confident in their engagements with the research process. In this way, the article suggests, disproportionate research attention may foster not research fatigue but a more knowing and co-productive research relationship.